Warp-knitted textiles with "hot wire" - Ehrmann, Andrea; Griesel, C. S.; Heimlich, R.; Weber, M. O. (Kettenwirk-Praxis)
Study on the possibilities of integrating strip conductors into knitwear, especially the integration of fine metal wires into warp-knitted structures